FORMATION OF ENVIRONMENTAL SAFETY CULTURE IN YOUNG PEOPLE AND ITS IMPORTANCE - Uzoqjonova Moxinur (Western European Studies, 2024)
This article provides information on promotion of environmental knowledge and safety culture among young people, involvement of advanced innovative technologies in the field of ecology
Keywords: Risk; safety; culture; life